The Routledge handbook of Asian security studies - Ganguly, Sumit; Scobell, Andrew; Liow, Joseph Chinyong (Routledge, Taylor & Francis Group, 2018)
The Routledge Handbook of Asian Security Studies provides a detailed exploration of security dynamics in the three distinct subregions that comprise Asia, and also bridges the study of these regions by exploring the geopolitical links between each of them. It examines these developments at both regional and national levels, including the conflict surrounding the South China Sea, the long-standing Sino-Indian border dispute, and Pakistan's investment in tactical nuclear weapons, amongst many others. This book will be of great interest to students of Asian politics, security studies, war and conflict studies, foreign policy and international relations generally.